Why have Anti-Offshore Tin Mining Movements Failed in Bangka but Succeeded in East Belitung? Political Opportunity Structures and Political Settlement in the Context of Indonesia's Democratic Future - Eko Bagus Sholihin (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
Civil society movements have occupied an important position in Indonesia's democratisation. This article seeks to determine why anti-offshore tin mining movements in the post-authoritarian era failed in Bangka but succeeded in East Belitung, an area where tin mining has historically been important. By analysing the political opportunity structures and political settlement mechanisms involved, this article argues, first, that the movement's success in East Belitung can be attributed to open political access, fragmentation within elite circles, and alliances with influential elites; such political opportunities were not available in Bangka. Second, in Bangka, the local bourgeoisie and brokers used clientelistic approaches in their political settlement and prevented resistance by co-opting local communities within the extraction chain. In East Belitung, meanwhile, such efforts were stymied by the lack of local bourgeoisie, the strength of environmental awareness, and the availability of alternative economic resources. It may thus be concluded that, while a clientelistic approach to settlement may prevent conflict, it also limits the political participation of civil society movements—an important element of democracy.